THE INCUBATION PROGRAMME AS AN INSTRUMENT FOR SUPPORTING BUSINESS IDEAS AT UNIVERSITY. AN EXAMPLE FROM POLAND: EXAMPLE FROM POLAND - Rudawska, Joanna (Management and Administration Journal, 2020)
Institutions of higher education play a key role in regional innovation support ecosystems. Their role, apart from prevailing education and research missions, is also to transfer knowledge and technology to business. This transfer may take place in various ways, and one of them is to support students, doctoral students and academics in developing innovative ideas within university incubators. Innovations are strongly associated with risk; that is why, it is so important to support any emerging idea at the first stage of its development. This role is played, among others, by university-based incubators as well as pre-incubation, incubation and post-incubation programmes they offer. The aim of this article is to discuss the typology and role of incubators in supporting business ideas and to characterise the phases of incubation process. The example of a pre-incubation programme from Polish universities presented in the article illustrates the course of the process and the support package offered to idea originators.